2009
DOI: 10.1016/j.jtcvs.2008.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Fatal complications of adult paraesophageal hernia: A population-based study

Abstract: Overall, most deaths were related to type III or IV hernias in aged patients with concomitant diseases, with those with severe symptoms requiring hospitalization at significant risk. Except for those at high surgical risk, we recommend repair of the paraesophageal hernia, at least in symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 19 publications
1
68
1
7
Order By: Relevance
“…[1][2][3] A recent (and large) population-based observational study identified a 16.4% risk of death when hospitalised symptomatic patients are treated conservatively. 2 Patients are often elderly and frail, 4 and so a balance of surgical risk and life expectancy is required when considering surgical repair. There is, however, ongoing uncertainty, in part owing to the lack of long-term follow-up studies in regard to the natural history of the condition and the durability of repair and symptom improvement.…”
mentioning
confidence: 99%
“…[1][2][3] A recent (and large) population-based observational study identified a 16.4% risk of death when hospitalised symptomatic patients are treated conservatively. 2 Patients are often elderly and frail, 4 and so a balance of surgical risk and life expectancy is required when considering surgical repair. There is, however, ongoing uncertainty, in part owing to the lack of long-term follow-up studies in regard to the natural history of the condition and the durability of repair and symptom improvement.…”
mentioning
confidence: 99%
“…[6,7]. Galimos komplikacijos: skrandžio apsisukimas 35-40 proc., skrandžio ir kitų organų įstrigi-mas bei šių organų nekrozė ir perforacija.…”
Section: įVadasunclassified
“…Diagnozavus šias komplikacijas, indikuotinas operacinis gydymas, tačiau net taikant operacinį gydymą, mirštamumas siekia > 50 proc. [2,3,4].…”
Section: įVadasunclassified
See 2 more Smart Citations